RESEÑA de: García, J.; Heras, B. de las; Peñuelas, E. Rehabilitación psicosocial, conceptos y estrategias. Oviedo : KRK, 1997 - Olabarría, Begoña (Revista de Psicopatología y Psicología Clínica, 1997)
-